Intestinal Inflammation Induced by Soybean Meal Ingestion Increases Intestinal Permeability and Neutrophil Turnover Independently of Microbiota in Zebrafish - Solis, Camila J.; Hamilton, M. Kristina; Caruffo, Mario; Garcia-Lopez, Juan P.; Navarrete, Paola; Guillemin, Karen; Feijoo, Carmen G. (Frontiers in Immunology, 2020)
A large number of the current medical therapies for inflammatory bowel disease that emerged from preclinical investigation in rodents failed to show beneficial effects in patients. Some of them induce severe side effects while in other cases they are simply not adequate to control the disease. Thus, there is a need for alternative animal models that offer complementary approaches that have not been exploited in rodents, thus contributing to a different view of the disease. Here, we report the effects of a soybean meal-induced intestinal inflammation model on intestinal integrity and function, as well as on neutrophil recruitment and microbiota composition in zebrafish. We found that the induced intestinal inflammation process is accompanied by an increase in epithelial permeability, in addition to changes in the mRNA levels of different tight junction proteins. Conversely, there was no evidence of damage of epithelial cells, nor an increase in their proliferation. Of note, our results showed that this intestinal inflammatory model is induced independently of the presence of microbiota. On the other hand, this inflammatory process affects intestinal physiology by decreasing protein absorption, increasing neutrophil replacement and altering microbiota composition with a decrease in the diversity of cultivable bacteria.